The prevalence and possible policy implications of the use of national and human security frames in climate-change-related reports, in South Africa’s print newspapers - Davis, Nerhene (University of Pretoria, 2022)
Mini Dissertation (MA (Environment & Society)--University of Pretoria, 2021.